1993
DOI: 10.1016/s0006-3495(93)81217-7
|View full text |Cite
|
Sign up to set email alerts
|

Rotational and translational water diffusion in the hemoglobin hydration shell: dielectric and proton nuclear relaxation measurements

Abstract: The dynamic properties of water in the hydration shell of hemoglobin have been studied by means of dielectric permittivity measurements and nuclear magnetic resonance spectroscopy. The temperature behavior of the complex permittivity of hemoglobin solutions has been measured at 3.02, 3.98, 8.59, and 10.80 GHz. At a temperature of 298 K the average rotational correlation time tau of water within a hydration shell of 0.5-nm thickness is determined from the activation parameters to be 68 +/- 10 ps, which is 8-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 34 publications
2
34
1
Order By: Relevance
“…Saturation transfer electron paramagnetic resonance studies have shown that the c value for rotational motion of the hemoglobin molecule is 8 × 10 −6 seconds when the hemoglobin molecule is encapsulated within the erythrocyte membrane (Cassoly, 1982). This is approximately 10 6 times slower than the rotational correlation time of bulk water (10 −12 − 10 −11 s) (Steinhoff et al, 1993 In the modified "complete model" for 17 O MR measurements (Fig. 1B), the vascular compartment of arteriole is replaced by artery because of the approximately identical H 2 17 O contents in arteriole and artery.…”
Section: General Considerationsmentioning
confidence: 99%
“…Saturation transfer electron paramagnetic resonance studies have shown that the c value for rotational motion of the hemoglobin molecule is 8 × 10 −6 seconds when the hemoglobin molecule is encapsulated within the erythrocyte membrane (Cassoly, 1982). This is approximately 10 6 times slower than the rotational correlation time of bulk water (10 −12 − 10 −11 s) (Steinhoff et al, 1993 In the modified "complete model" for 17 O MR measurements (Fig. 1B), the vascular compartment of arteriole is replaced by artery because of the approximately identical H 2 17 O contents in arteriole and artery.…”
Section: General Considerationsmentioning
confidence: 99%
“…If the c value of 8.5 Â 10 À12 s for bulk water at 298 K is used, 3 then estimated 17 O T 2 and T 1 according to eqn (2) should be between 2.8 ms (for ¼ 0) and 2.1 ms (for ¼ 1). This estimation indicates that the 17 O relaxation times of water are extremely short, in the range of few milliseconds.…”
Section: O Spin Relaxationmentioning
confidence: 99%
“…Such hydration water with the lowered DR frequency is called looselybound water or constrained water. So far, studies on the constrained water of proteins in aqueous solution were carried out to understand thermodynamic stability and functions of proteins such as myoglobin, ribonuclease A, hemoglobin, horse heart cytochrome c, bovine serum albumin, ovalbumin and ubiquitin [13][14][15][16][17][18][19]. Our studies on aqueous actin filament solutions demonstrated the presence of the hypermobile water in addition to the constrained water [20,21].…”
Section: Introductionmentioning
confidence: 81%